Main instruments used to measure social skills in different contexts: integrative review (Research, Society and Development, 2021)
The term Social Skills was used to describe the way a person behaves appropriately in different types of environments, people, groups and communities. The aim of this study was to identify the main instruments used to measure HGS in different contexts. This is an integrative literature review in the Scielo, LILACS and PubMed databases, using the descriptors: Social Skills, Social Skills Inventory and Social Behavior. The inclusion criteria were articles published in the last five years (2015 to 2020), which were available online, in their entirety and free of charge, and which addressed information about the use of HS measurement tools. Editorials, letters to the editor, theses, dissertations, monographs and course conclusion papers that did not meet the objective of the study, as well as articles repeated in more than one database, were excluded. Fifteen articles were identified, grouped into three thematic categories: HS instruments used in adults; HS instruments used on children and adolescents and HS instruments used ​​on university students, interns and residents. The review identified that the main instrument used was the Del Prette and Del Prette Social Skills Inventory. These instruments offer an opportunity for early diagnosis and facilitate the planning of intervention strategies. The studies found indicate the need for more research with greater methodological rigor on the assessment of social skills in different contexts.